Cultural relevance and informal reading inventory performance: African-American primary and middle school students. Issue 2 (3rd April 2018) - Christ, Tanya; Chiu, Ming Ming; Rider, Stephanie; Kitson, Deborah; Hanser, Katherine; McConnell, Elizabeth; Dipzinski, Renae; Mayernik, Heather
ABSTRACT: We explore whether (a) teacher ratings of texts' cultural relevance along various dimensions differ from those of students, (b) these ratings reflect a single construct, and (c) ratings of specific dimensions are related to specific reading outcomes. Fifty African-American students were each administered two text protocols for a total of 100 protocols. Teachers and students rated each text along multiple dimensions of cultural relevance. Factor analyses showed that teachers' cultural relevance ratings formed a coherent construct, but students' ratings did not. Multivariate, multilevel, mixed response analyses showed that students who rated places and experiences as culturally relevant had higher critical evaluation and connection scores. When researcher ratings were higher, students' word recognition meaning-maintenance, rereading at miscues, and literal comprehension scores were higher.